Histatina 5 e novas estratégias no combate à Candida albicans - Zolin, Gabriela Vieira Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Oral candidiasis is one of the most common fungal infections in the oral cavity, affecting mostly patients with immunologic system suppressed by diseases like HIV and cancer. Candidiasis is caused by species from Candida gender, especially Candida albicans, which are presented as a polymorphic commensal fungi that can be found naturally in the microbiota of human population. Through morphological transition between yeast and hyphal cells, C. albicans is capable of starting an infection that, although happens most commonly in mucosal tissues, can disseminate through blood becoming a systemic infection, which presents high morbidity and mortality rates. An aggravant of C. albicans infections is the resistance that has been developing in the last decades for antifungal medicine used in treatments to combat the infection. In fact, antimicrobial resistance is considered by WHO as one of ten biggest human health threats the world faces nowadays. Therefore, the search for new antifungal agents capable of overcoming the antifungal resistance barriers is urgent and essential. Histatin 5 is a 24 amino acid antimicrobial peptide of histatin family, that can be found naturally in human saliva, and presents a potent antifungal activity against C. albicans cells, being then a potential antifungal agent of great interest. Histatin 5 activity can be impaired for interaction with molecules present in the oral cavity, and some resistance mechanisms to its action has already been observed in C. albicans cells Thus, there are many proposals in development aimed at increasing efficiency antifungal for histatin 5. This work presents some of these proposals, involving metal-peptide complexes and nanoparticles carriers as an alternative to fighting the important oral candidiasis pathogen, C. albicans.

A candidíase oral é uma das infecções fúngicas mais comuns na cavidade oral, afetando principalmente pacientes que têm o sistema imunológico suprimido por doenças como HIV e câncer. A candidíase é causada por espécies do gênero Candida, especialmente Candida albicans, que se apresenta como um fungo polimórfico comensal que pode ser encontrado naturalmente na microbiota de boa parte da população mundial. Através da transição morfológica entre os estados de levedura e de hifas, C. albicans é capaz de desencadear uma infecção, que, embora mais comum em mucosas, pode se espalhar através do sangue tornando-se uma infecção sistêmica, que possui altas taxas de morbidade e mortalidade. Um agravante às infecções causadas por C. albicans é a resistência que vem desenvolvendo ao longo das últimas décadas aos medicamentos antifúngicos utilizados em seu combate. De fato, o problema da resistência antimicrobiana é considerado pela OMS como uma das 10 principais ameaças à saúde pública que a humanidade enfrenta atualmente. Assim, a busca por novos agentes antifúngicos capazes de superar as barreiras de resistência apresentadas pelo fungo é urgente e essencial. A histatina 5 é um peptídeo antimicrobiano composto por 24 resíduos de aminoácidos, pertencente à família das histatinas, que é encontrado naturalmente na saliva humana, e apresenta forte atividade antifúngica contra células de C. albicans, o que a torna um potencial agente para terapia antifúngica de grande interesse. A atividade antifúngica da histatina 5 pode ser prejudicada por interações com moléculas presentes na cavidade oral, e alguns mecanismos de resistência à sua ação já foram observados nas células de C. albicans. Assim, existem diversas propostas em estudo que visam aumentar a eficiência antifúngica da histatina 5. Este trabalho apresenta algumas propostas envolvendo a complexação do peptídeo com íons metálicos e o uso de nanopartículas carreadoras, como alternativa ao combate do importante causador de candidíase oral, C. albicans.
Histatin 5 and new strategies against Candida albicans
Keywords: Agentes antifúngicos; Histatina 5; Candida albicans